Prognosis, rehabilitation and outcome after inflicted brain injury in children -- a case of professional developmental delay. - Johnson DA; Rose D (Pediatric Rehabilitation)
Reported outcomes after child brain injury are variable, creating difficulties for predicting individual needs and service provision. In the UK, prognosis for children surviving early brain injury is characteristically optimistic. Communication between hospital and community agencies is poor. There is little regard for facilitating optimal recovery, and even less for supporting the child's further learning and development. The problem persists in spite of accumulating clinical and scientific evidence over the last 100 years. The consequences are wide-ranging and detrimental to the physical and mental health of the child and family. The disabled child becomes a progressively handicapped adult. Long-term outcome in old age may be unnecessarily compromised. The social and economic costs will be correspondingly and unnecessarily high.